Combining environmental gradients to explain and predict the structure of demersal fish distributions - Chatfield, B.; Van Niel, K.; Kendrick, G.; Harvey, Euan (Blackwell Publishing, 2010)
Species distribution modelling was used to investigate relationships betweenbenthic environmental variables and patterns of demersal fish speciesdistributions using fish occurrence data collected from spatially sparse pointsampling. Our goals were to determine: (1) the relative importance of differentenvironmental variables, (2) whether accurate predictions can be developed fromthese models, and (3) how a comparison of the models against known speciesecology can be used to assess model relevance and to provide further insights thatcould drive future studies of these species.